Preparation and Characterization of Some Metal Complexes of the New Ligand : 2-[ 2-(5- Methyl benzothiazolyl )azo] -4-Methyl phenol ( 5-Me-BTAC ). - Mehdi, R.T.; Ali, A. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
This work reports the synthesis and characterization of some Co(111), Ni(11), Cu(11), Zn(l 1), Cd(1 1) and Hg(11) chelates of the new benzothia-zolylazo Ligand ( 5-Me-BTAC ) . The compounds were Characterized by IR , electronic spectroscopy, magnetic susceptibility ,elemental analysis and molar conductance measurements . The elemental analysis suggest the formula [ ML2 ] x.nH2O where x=Cl , n=1 for M= Co(111) and x=o , n=o for the remaining metal ions Electronic spectra and magnetic susceptibility data has supported the proposed octahedral geometry of Co(111) Ni(11) and Cu(1 I) Complexes. Conductivity measurements refer to nonionic structure of these Complexes except of Co(111) .